THE USE OF GAMES TO TEACH ENGLISH FOR ELEMENTARY SCHOOL STUDENTS: THE PERCEPTION OF PRE-SERVICE TEACHERS AT ENGLISH EDUCATION DEPARTMENT OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Aprillia Dwi Fitriani (PBI 15 UMY 067, 2015)
*67 Elementary school students have attention span which make them only can focus for 10-20 minutes. The researcher experiences in internship program found that games give positive impacts for children in learning because games made students learn a language better as learning becomes natural for them. This research was conducted with the aim to investigate the perception of pre-service teachers at English Education Department (EED) of Universitas Muhammadiyah Yogyakarta (UMY) on the use of games to teach English for elementary school students. The researcher used qualitative design to achieve the purpose of the research. There were five students from batch 2014 as the research participants. The researcher chose in-depth interview to elicit information from participants. The data from interview were analysed by coding which were validated through member checking. The findings showed that the pre-service teachers’ perception on the types of games, the advantages and the disadvantages of games to teach English for elementary students. The types of games the pre-service teachers commonly used were a whispering game, guessing that pictures, spelling bee, guessing word, describing the picture, chart games and colors in the air games to teach English for elementary school students. Other finding revealed that games as a teaching strategy give advantages on the students’ skills, students’ subskills, students’ softskill, and efficient implementation of games. The findings also exposed that games have disadvantages as a teaching strategy. The disadvantages of games were games made ineffective class circumstance, students’ lack of attention, difficulty of grammar practice, and games have challenging level.